Praktik Akumulasi Lebenswelt Sebagai Basis Strategi BUMDes Yang Berkelanjutan - Ahmad Imron Rozuli (Jurnal Transformative)
In line with the emergence of constitutional frameworks that are designed to improving village development, there has been a significant increase in the presence of village economic institutions such as BUMDes in Indonesia. Yet, this institutional emergence quantitatively is not always followed by the increasing of quality and professional management of economic resource for the welfare of local communities. Specific factor such as weak empowerment, corrupt behavior of local elites and low capacity of resource management are still challenges faced in order to strenghthen the capacity of village economic institutions and in order to create a sustainable BUMDes. Based on local development experience at Gondowangi Village, in Wagir District, Malang Regency, this study intend to explain what sociological scholarship called as a lebenswelt (community knowledge) which serves as a main basis for village development planning and sustainable BUMDes maintanance strategies. This research uses a qualitative descriptive method combined with the perspective of communicative action theory which promoted by Jurgen Habermas. This research argue that there is three important factors influence the success of the practice of accumulating community knowledge in village development planning, namely, first: the leadership factor, secondly: mapping problems and potentials based on community participation, and third: the invovement of external group that can encourage innovation in the local communities.